1866 Ky. Acts 715 - (:unkn) unknown (My University, 1866)
An Act to Amend the Charter of the Town of New Castle, ch. 819§ 2: If any person shall shoot off a gun or pistol within the corporate limits of said town, it shall be the duty of the trustees and officers of said town to report the fact to the police judge, who shall forthwith have the person so offending arrested and brought before him for trial, and, on conviction of the offense, shall be fined by said judge in a sum not to exceed ten dollars, and a forfeiture to said town of the gun or shall be the duty of said judge to have the gun or pistol so used sold at public auction, and the proceeds thereof shall be paid into the treasury of said town . . . .
Keywords: DISCHARGE